Relationships between bullies, victims and mental health among adolescents in Maldives - Aishath, Nasheeda (2016)
The main purpose of this research is to examine the relationships between bullies, victims and mental health among adolescents in Maldives. The study investigates the types of bullying and victimization common among adolescent boys and girls. The study also investigate the types of mental health among adolescents in Maldives. Furthermore, this study also investigates the moderating effects of gender and age on the relationship between bullies, victims and mental health among adolescents in Maldives. The research adopts a cross sectional quantitative survey method. Adolescents Peer Relation Inventory (APRI) for bullying and Mental Health Index (MHI38) were used as research instruments. A total of 460 survey questionnaires were analyzed in this study. The target group of this study were adolescents between 11 to 16 years. Data were collected from 8 different schools from three provinces in Maldives. Descriptive data were analyzed using IBM SPSS version 22 and inferential analysis were done using AMOS version 20. Findings on descriptive analysis of bullying behavior indicated that 84% males and 76% females bully others. Verbal bullying is the most common type of bullying among males and females. Findings on victimization suggests that 85% of adolescents have been targets to all forms of bullying. Fifty five percent of adolescents report weak or poor emotional relationships with significant others in their life, while 37% reveals they have low positive affect. The global mental health index of the adolescents in Maldives suggest 24% have poor psychological wellbeing. Findings on the relationship between bullying others and mental health revealed a nonrecursive relationship whereby, bullying others and mental health have significant negative relationship (-.96) and mental health and bullying others have a significant positive relationship (.96).This finding suggests that individuals with poor mental health end up being bullies. Likewise, findings on victimization and mental health reveal that being targets to bullying have a significant positive relationship with mental health. The notion supports biopsychosocial model of stress, as bullying is a stressful event which leaves the individual very vulnerable and helpless. Thus, these feeling will cause negative thoughts which will affect their mental state. Thus, the relationship of bullying and mental health phenomena can be explained in light with Biospychosocial model. However, findings on moderating factors on the relationship revealed that age and gender does not moderate on this relationship. This research will serve as a platform for school authorities and policy makers in developing effective intervention strategies to reduce bullying, victimization and mental health concerns.